INCREASING PRODUCT SALES THROUGH DIGITAL MARKETING AND BRAND AWARENESS IN THE DIGITAL ERA - Sudirjo, Frans; Hendrayani, Eka; Djakasaputra, Arifin; Juliana, Juliana; Alimin, Erina (ITB AAS Indonesia Surakarta, 2024)
This research is motivated by the importance of product sales to increase revenue, create profits and support company growth. The aim of this research is to determine and analyze the increase in product sales through digital marketing and brand awareness in the digital era. The research design used in this research is descriptive quantitative with a survey method, collecting research data using a questionnaire. The population in this study is the Indonesian population who fall into the age category of generation Z and the millennial generation who use Uniqlo products. The sample in this study was 100 people. The instruments used have been tested for validity and reliability. The collected data was tested using the classic assumption test and multiple linear regression test. The results of this research show that 1) Digital marketing has a positive and significant effect on product sales in the digital era, 2) Brand awareness has a positive and significant effect on product sales in the digital era, and 3) Digital marketing and brand awareness have a positive and significant effect on product sales in the digital era. The findings of this research suggest that if a company wants to increase product sales, the company must also increase digital marketing and brand awareness.